Functional modulation of atrio-ventricular conduction by enhanced late sodium current and calcium-dependent mechanisms in Scn5a1798insD/+ mice - Rivaud, Mathilde R; Marchal, Gerard A; Wolswinkel, Rianne; Jansen, John A; van der Made, Ingeborg; Beekman, Leander; Ruiz-Villalba, Adrián; Baartscheer, Antonius; Rajamani, Sridharan; Belardinelli, Luiz; van Veen, Toon A B; Basso, Cristina; et al. (Oxford University Press, 2020)
Aims: SCN5A mutations are associated with arrhythmia syndromes, including Brugada syndrome, long QT syndrome type 3 (LQT3), and cardiac conduction disease. Long QT syndrome type 3 patients display atrio-ventricular (AV) conduction slowing which may contribute to arrhythmogenesis. Methods/Results: We assessed electrophysiological and molecular alterations underlying AV-conduction abnormalities in mice carrying the Scn5a1798insD/+ mutation (mutants). Langendorff-perfused mutants hearts showed prolonged AV-conduction compared to wild type (WT) without changes in atrial and His-ventricular (HV) conduction. The late sodium current (INa,L) inhibitor ranolazine (RAN) normalized AV-conduction in mutants mice, likely by preventing the mutation-induced increase in intracellular sodium ([Na+]i) and calcium ([Ca2+]i) concentrations. Indeed, further enhancement of [Na+]i and [Ca2+]i by the Na+/K+-ATPase inhibitor ouabain caused excessive increase in AV-conduction time in mutants hearts. Mutants mice from the 129P2 strain displayed more severe AV-conduction abnormalities than FVB/N-mutants mice, in line with their larger mutation-induced INa,L. Transverse aortic constriction (TAC) caused excessive prolongation of AV-conduction in FVB/N-Scn5a1798insD/+ mice (while HV-intervals remained unchanged), which was prevented by chronic RAN treatment. Mutants-TAC hearts showed decreased mRNA levels of conduction genes in the AV-nodal region, but no structural changes in the AV-node or His bundle. In mutants-TAC mice deficient for the transcription factor Nfatc2 (effector of the calcium-calcineurin pathway), AV-conduction and conduction gene expression were restored to WT levels. Conclusions: Our findings indicate a detrimental role for enhanced INa,L and consequent calcium dysregulation on AV-conduction in Scn5a1798insD/+ mice, providing evidence for a functional mechanism underlying AV-conduction disturbances secondary to gain-of-function SCN5A mutations.
Keywords: Atrio-ventricular block/conductionSCN5A; Calcium homeostasis; Late sodium current; NaV1.5; Mutations